Phenolic Content and Antioxidant Activity of Black Glutinous Rice Anthocyanin during Fermentation by Pediococcus pentosaceus N11.16 - Nanik Suhartatik; Akhmad Mustofa; Ponco Mursito (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Anthocyanin was developed into natural food colorant in microemulsion systems to improve their stability and readiness for food preparation. Anthocyanin has an antioxidant activity. The degradation of anthocyanin into small compound could increase the biological activity. Anthocyanin was extracted from black glutinous rice and prepared using food grade surfactant such as Tween 80, Tween 20, and Span 80. Microemulsion was then added into modified deMann Rogosa Sharp (MRS) medium as much as 5, 10, 15, 20 and 25 ppm. Lactic acid bacteria genus Pediococcus pentosaceus N11.16 were grown for 18–24 hours and were used as enzyme producers. This experiment was aimed to determine the stability of anthocyanin in microemulsion systems to enzymatic degradation. The modified MRS medium was added with microemulsion and incubated for 24 h. Phenolic content remained stable during the fermentation process in all treatments, while the highest antioxidant activity was found in the sample with 20 ppm of anthocyanin. Total acid-producing bacteria were also monitored during the incubation and the result showed that there was a decline in their growth. There was a significant change in the antioxidant activity during incubation.